A Case Of Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC) Presenting with Dizziness-A Rare Case Report - Adhikari, Suman; Jha, Sunil Chandra; Gajurel, Ratna Mani; Paudel, Chandra Mani; Acharya, Subarna Mani; Thapa, Sanjeev; Khanal, Raja Ram; Thapa, Shovit; Yadav, Vijay; Sharma, Manju; et al. (Journal of Advances in Internal Medicine, 2020)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a genetic disorder. Its hallmark is the fibrofatty replacement of myocardium leading to cardiomyopathy. It can have various presentations which can range from silent disease to sudden cardiac death. Here, we report a case of ARVC in a 42 years old female who presented to us with dizziness as her first clinical presentation. We clinched the diagnosis with the help of electrocardiogram, echocardiography and cardiac magnetic resonance imaging (CMR).